The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s13287-020-02045-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of ovine bone marrow-derived stromal cells (oBMSC) and evaluation of chondrogenically induced micro-pellets for cartilage tissue repair in vivo

Abstract: Bone marrow stromal cells (BMSC) show promise in cartilage repair, and sheep are the most common large animal pre-clinical model. Objective The objective of this study was to characterise ovine BMSC (oBMSC) in vitro, and to evaluate the capacity of chondrogenic micro-pellets manufactured from oBMSC or ovine articular chondrocytes (oACh) to repair osteochondral defects in sheep. Design oBMSC were characterised for surf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…However, transplantation of hypoxic BM-MSC cultures into ovine articular cartilage defects produced no benefits compared to normoxia [ 94 ]. BM-MSC micro-pellets cultured under hypoxia in a chondrogenic medium were stained for GAG but showed elevated COL10 and RUNX2 levels compared to AC micro-pellets [ 95 ]. Generally, hypoxic conditions have pro-chondrogenic and anti-inflammatory impacts on stem cell cultures, while negative effects on cell viability are not observed [ 96 ].…”
Section: Bone-marrow-derived Mesenchymal Stem Cellsmentioning
confidence: 99%
“…However, transplantation of hypoxic BM-MSC cultures into ovine articular cartilage defects produced no benefits compared to normoxia [ 94 ]. BM-MSC micro-pellets cultured under hypoxia in a chondrogenic medium were stained for GAG but showed elevated COL10 and RUNX2 levels compared to AC micro-pellets [ 95 ]. Generally, hypoxic conditions have pro-chondrogenic and anti-inflammatory impacts on stem cell cultures, while negative effects on cell viability are not observed [ 96 ].…”
Section: Bone-marrow-derived Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The findings reported by Doran and his study group members in 2021 [ 29 ] also demonstrated the efficiency of using cartilaginous differon cells for articular cartilage tissue restoration. Obtained results demonstrate the prospect for further use of demineralized human spongiosa for articular hyaline cartilage defects repair.…”
Section: Resultsmentioning
confidence: 77%
“…Over the past 30 years, MSCs have become a cornerstone of tissue engineering and biotechnology research, having been used in a variety of scenarios, such as evaluating the optimum cell dose for treatment of non-union bone fractures [37] and evaluating the capacity of MSCs for managing osteochondral defects [38]. There has recently been increasing interest in the use of MSCs and their derived EVs for tendon and ligament repair, presenting the need for a review of the current literature in this field.…”
Section: Discussionmentioning
confidence: 99%